Pace of Life Is Faster for a Bored Person: Exploring the Relationship Between Trait Boredom and Fast Life History Strategy - Garam Kim; Eunsoo Choi (Evolutionary Psychology)
Life history theory suggests that in harsh, unpredictable environments, individuals may benefit from adopting a fast life history strategy. This may involve experiencing boredom more frequently and intensely as an adaptive mechanism to seek novel stimuli, potentially increasing the number of sexual partners and offspring. This study explored the relationship between trait boredom—a chronic characteristic of feeling bored—and fast life history strategies. Our findings confirmed a positive association between boredom proneness and fast life history strategies at both individual and country levels. In Study 1, fast life history strategy was positively correlated with boredom proneness and mediated the relationship between perceived childhood support/resources and boredom proneness. In Study 2, we conducted a multi-level analysis using secondary data from 15 countries. The results showed that countries with higher boredom proneness scores showed more indicators of faster life history strategies. These results suggest that trait boredom may be a functional characteristic of fast life history strategists. This study is the first empirical investigation of trait boredom within a life history framework, highlighting trait boredom's functional role from evolutionary and ecological perspectives.